2020
DOI: 10.1007/s11433-019-1477-7
|View full text |Cite
|
Sign up to set email alerts
|

Holographic topological semimetals

Abstract: The holographic duality allows to construct and study models of strongly coupled quantum matter via dual gravitational theories. In general such models are characterized by the absence of quasiparticles, hydrodynamic behavior and Planckian dissipation times. One particular interesting class of quantum materials are ungapped topological semimetals which have many interesting properties from Hall transport to topologically protected edge states. We review the application of the holographic duality to this type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 96 publications
3
29
0
Order By: Relevance
“…So it should be careful if one wants to consider pseudo-spontaneous regime where m 2 1 and β m 2 for a non-trivial Y (X). 8 In contrast, for the case without magnetic field, the inequality (3.12) is satisfied automatically since k 0. Thus one is not able to obtain any constraint from (3.12) when B = 0.…”
Section: )mentioning
confidence: 98%
See 2 more Smart Citations
“…So it should be careful if one wants to consider pseudo-spontaneous regime where m 2 1 and β m 2 for a non-trivial Y (X). 8 In contrast, for the case without magnetic field, the inequality (3.12) is satisfied automatically since k 0. Thus one is not able to obtain any constraint from (3.12) when B = 0.…”
Section: )mentioning
confidence: 98%
“…The key message is that by taking into account magnetic field, we are able to give a generic constraint on k, without referring to the non-linear details of the coupling functions Y and V . 8 To obtain the constraint (3.13), we have only considered a very generic expansion (3.6) and demanded σ xx 0 in the weak disorder limit. As one can see from (3.1) and (3.2) that the behaviors of the magnetotransport depend on the details of couplings in a theory.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Holography has been applied to the study of the topological nature in Weyl semimetals [7] and nodal line semimetals [8,9] which uncovered lots of novel properties of topological semimetals at strong coupling [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. See [26] for a recent review on this topic.…”
Section: Jhep05(2021)141mentioning
confidence: 99%
“…Other aspects of the holographic Weyl semimetal have been explored in [26][27][28][29][30][31][32][33]. A recent review on the holographic Weyl semimetals can be found in [34].…”
Section: Introductionmentioning
confidence: 99%